Jejunal Choristoma: A Very Rare Cause of Abdominal Pain in Children - T. A. Olajide; S. O. Agodirin; R. W. Ojewola; O. O. Akanbi; T. O. Solaja; Johnson Oluremi Odesanya; O. O. Ariyibi (Case Reports in Surgery)
Choristoma is development of a normal tissue in an aberrant location. This report describes jejunal salivary choristoma (JSC) causing recurring episodes of abdominal discomfort in a 5-year-old girl. Exploratory laporatomy revealed a pale yellow subserosal jejunal lesion. Wedge resection of the lesion and repair of the bowel were performed. The child did well postoperatively and has since that time been free of pain at follow-up. Histopathological examination of the resected lesion revealed salivary gland choriostoma. Literature review (PUBMED search engine) revealed no previous report of this rare clinicopathologic entity. We conclude that choriostoma should be considered a possible differential when evaluating abdominal complaint in children.